Study on lung infections of patients with cancer under chemotherapy - Abdul Sattar, Safana; Al Mallah, Nawar (Iraqi Journal of Science, 2019)
The aim of this study is to assess the prevalence of lung infections among a group of hospitalized cancer patients who received chemotherapy as well as to describe a population of these patients. The clinical data and demographic information were collected from the archived files of in-patients referred to hematology center / Baghdad Teaching Hospital / Medical City , ministry of health, Iraq during the period of 2018. This study was carried out on 250 patients with different types of cancer ,they were mostly of age group (40 - 49) 59 / 250 (23.6)% , (14-19) 49 /250 (19.6%) and (60-69) 41/ 250(16.4%) . The patients had two major types of hematological malignancies: leukemia 109/250(43.6%) and lymphoma 105/250(42%), only 36/250 (14.4%) of the patients had other types of cancer which were distributed as : 26/250( 10.4 %) microangiopathic and 10 /250 (4 %) Multiple myelomoa. Statistically , there was significant correlation between age parameter and types of cancer in p<0.05 (p value : 0.000). Patients with positive Lung infections , as recorded on their medical reports, were not in high frequency and found only in 48/250(19.2%) of the cases which were mostly shown in patients with leukemia 28/48( 58.3 %) .In spite of that there was no significant correlation between lung infections and type of cancer .The higher percentage of patients, who admitted to the women wards of Baghdad hospital, came from Baghdad city 132/250(52.8%) and diyala governorate 45/250(18%). The married women were 173 /250(69.2%) and mostly they were housewives 200/250(80%). The illiteracy was in 67/250(26.8% ) of patients. Low frequent lung infections as resulted during this study could be because of the good control of infections by giving suitable antibiotic drugs for the bacterial infections but most of patients with positive cases may be infected with viruses or fungi ,which are difficult to diagnose and treat . These infections occurred due to the immune defects induced by chemotherapy treatments . So the greatest hope for the future is the availability of more targeted anticancer drugs that have fewer side-effects on the immune system.